Effect of Blanching on Drying Kinetics and Quality of Solar Dried Cabbage - Sharma, Pratibha; Akbari, S.; Shrivastava, M.; Kumar, Vishal (Journal of Agricultural Engineering, 2014)
Cabbage (Brassica oleracea var. capitata) 250 g samples were blanched in water at 100ËšC for 2 min, and subjected to solar cabinet drying to observe qualitative changes of the dried product. Blanching pre-treatments were done in plain water for 2 min (T1), and 0.5% potassium metabisuphite (T2). Sample without blanching was considered as control(UT). The samples were then dried in a solar cabinet dryer (57 Â±3ËšC) . Six thin layer drying models were used to fit the experimental moisture ratio obtained for cabbage by nonlinear regression analysis using NLREG Statistical programme. Page model showed a good fit with the highest correlation for cabbage samples. Solar cabinet dried product were found good and acceptable in sensory quality. Cabbage blanched in KMS solution was the best, followed by blanching in water. The rehydration ratio (5.5) and coefficient of rehydration (0.488) were highest for cabbage blanched with KMS solution among all samples. The result showed that the rehydrated products could be well utilized for substituting the fresh product in off-season.